A sociometric examination of perceptions of the impact of contemporary tourism upon society in the tourist resort of “Ayia Napa”, cyprus. A qualitative approach - Saveriades, Alexis (My University, 2007)
Research in the field of residents’ perceptions and attitudes on the social impact of tourism’ conducted over the last decades considers tourism as a disruptor of traditional social structures and behavioural patterns. Furthermore, tourism seems to be blamed for all the ill fates of modern societies. However, the base knowledge about resident attitudes comes from the analysis of quantitative surveys, which ask respondents to indicate a level of agreement with positive or negative statements about the impact of tourism, as if people think in ‘tick-boxes’ and ‘Likert-type’ scales. This paper presents a different methodological approach altogether, where focus group discussions are employed as the main research instrument, and the participating groups were not informed that the actual scope of the study was related to the subject of tourism and its effects on their family life. Instead, the study was furnished upon the subjects, as a ‘survey on social change in family life in the Ayia Napa region over a 30-year period’ in an attempt to indirectly identify the degree to which such changes are attributed to tourism.
Keywords: Ixodida